A Novel Theranostic Strategy for Malignant Pulmonary Nodules by Targeted CECAM6 with 89Zr/131I‐Labeled Tinurilimab - Chongyang Chen; Keying Zhu; Jing Wang; Donghui Pan; Xinyu Wang; Yuping Xu; Junjie Yan; Lizhen Wang; Min Yang (Advanced Science)
Abstract Lung adenocarcinoma (LUAD) constitutes a major cause of cancer‐related fatalities worldwide. Early identification of malignant pulmonary nodules constitutes the most effective approach to reducing the mortality of LUAD. Despite the wide application of low‐dose computed tomography (LDCT) in the early screening of LUAD, the identification of malignant pulmonary nodules by it remains a challenge. In this study, CEACAM6 (also called CD66c) as a potential biomarker is investigated for differentiating malignant lung nodules. Then, the CEACAM6‐targeting monoclonal antibody (mAb, tinurilimab) is radiolabeled with 89Zr and 131I for theranostic applications. In terms of diagnosis, machine learning confirms CEACAM6 as a specific extracellular marker for discrimination between LUAD and benign nodules. The 89Zr‐labeled mAb is highly specific uptake in CEACAM6‐positive LUAD via positron emission tomography (PET) imaging, and its ability to distinguish in malignant pulmonary nodules are significantly higher than that of 18F Fluorodeoxyglucose (FDG) by positron emission tomography/magnetic resonance (PET/MR) imaging. While the 131I‐labeled mAb serving as the therapeutic aspect has significantly suppressed tumor growth after a single treatment. These results proves that 89Zr/131I‐labeled tinurilimab facilitates the differential capacity of malignant pulmonary nodules and radioimmunotherapy of LUAD in preclinical models. Further clinical evaluation and translation of this CEACAM6‐targeted theranostics may be significant help in diagnosis and treatment of LUAD.